2017
DOI: 10.1007/s00417-017-3836-1
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept in diabetic macular edema refractory to previous bevacizumab: outcomes and predictors of success

Abstract: Conversion to aflibercept for persistent DME resulted in functional and anatomical improvements and these outcomes were not influenced by previous bevacizumab exposure. Pre-switch CMT was a predictor of anatomical changes after aflibercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…This is the first 2-year prospective study of aflibercept for DME conducted in a routine clinical situation in patients with no or minimal recent exposure to anti-VEGF treatment. The few clinic-based prospective T&E studies conducted to date have investigated the efficacy of bevacizumab [22] or ranibizumab [23][24][25], but most prospective studies have concentrated on the outcomes of aflibercept treatment in patients non-responsive to other anti-VEGF treatments [26][27][28][29] or using loading followed by an 8-weekly regimen [30], with results similar to that observed in the VIVA/VISTA.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first 2-year prospective study of aflibercept for DME conducted in a routine clinical situation in patients with no or minimal recent exposure to anti-VEGF treatment. The few clinic-based prospective T&E studies conducted to date have investigated the efficacy of bevacizumab [22] or ranibizumab [23][24][25], but most prospective studies have concentrated on the outcomes of aflibercept treatment in patients non-responsive to other anti-VEGF treatments [26][27][28][29] or using loading followed by an 8-weekly regimen [30], with results similar to that observed in the VIVA/VISTA.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the DRCR.net protocol T study revealed that the incidence of persistent DME after 3 consecutive monthly injections was 50.8%, 53.2% and 72.9% through week 12, and 31.6%, 41.5% and 65.6% through week 24 in eyes that received aflibercept, ranibizumab and bevacizumab, respectively. Different treatment strategies have been proposed for PDME including switching to a different anti-VEGF agent, changing to intravitreal corticosteroid, focal laser treatment, and use of other adjunctive treatments like antioxidants [15,16,18,19]. There is increasing data in the literature that show continued treatment with the same anti-VEGF drug may lead to both functional and anatomical improvement in the longer term [10].…”
Section: Discussionmentioning
confidence: 99%
“…Centerinvolved DME was defined as central retinal thickness (CRT) ≥ 300 μm by Cirrus OCT (Carl Zeiss Meditec, Dublin, CA, USA) at the beginning of the study [4,15]. Diabetic eyes with evidence of residual intraretinal and/ or subretinal fluid and CRT on OCT > 300 μm after receiving loading doses of 3 monthly intravitreal anti-VEGF injections were considered to have PDME [16,17]. The final cohort included eyes that either continued the same initial anti-VEGF drug after they met previous criteria for PDME as group 1, and eyes with two successive cycles of switching anti-VEGF drugs (double anti-VEGF switch) as group 2.…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study, 49 eyes from 34 patients with DME refractory to bevacizumab were treated with intravitreal aflibercept injection. 37 All patients had at least 3 intravitreal bevacizumab injections before switching to aflibercept, and all patients were followed-up for at least 3 months after switching. The mean visual acuity improved from 0.55 logMAR to 0.46 logMAR (P = 0.038), and the mean CMT decreased from 437 µm to 349 µm (P < 0.001).…”
Section: Anti-vegf Switchingmentioning
confidence: 99%